Seasonal incidence and management of Clostera cupreata (Butler) (Lepidoptera: Notodontidae) on Populus deltoides - Sangha, K.S.; Dhaliwal, Ashwinder K.; Singh, Ravinder (Indian Journal of Agroforestry, 2020)
The host range, seasonal fluctuation in incidence, natural enemies and management of Clostera cupreata were studied in Punjab. Apart from poplar, larvae were fed on the leaves of Salix spp. The incidence of C. cupreata (based on per cent damaged leaves and pupae of C. cupreata) having its peak in September (46.48% & 3.73) was observed from April (3.00% & 0.64) to December (24.54% & 2.28). The mean damaged leaves and pupae of C. cupreata were found to be significantly lower in intercropped (20.76% & 1.59) than fallow plantations (27.82% & 2.39) of poplar. The feeding of C. cupreata was minimum on PL 7 (27.17 cm2) which being at par with L 47/88 (27.49 cm2) was significantly lower than G 48 clone (27.93 cm2). Among natural enemies, larval parasitoid, Aleoides percurrens emerged from the field collected eggs and larvae of C. cupreata; and a predatory bug, Canthecona furcellata was found to be feeding on the larvae of C. cupreata. The insecticides viz. quinalphos, profenofos and carbaryl @ 0.1 per cent concentration kept the population of C. cupreata under check up to 21 days after spraying.